Spatial Development of Innovation Systems in Russia - Arkhipova, Lidija Sergevna (Olsztyn Economic Journal, 2014)
While the development of the country's national innovation system as a whole is very important and should be prioritized, its regional aspect is even more important. The specifics of the Russian Federation's transition to an innovation-based economy is in that that, at the present time, prioritized is the need to ensure the effective development of those economy sectors that underlie the country's specialization and may provide regional and national competitive advantages. To such sectors belong the chemical industry, machine-building and power energetics. We would like to note that initial innovation awareness indicators in the regions are comparable and do not differ greatly but the growth of activity can be observed only in some of the regions. The problem of large differentiation among the constituent entities of the Russian Federation by their level of economic development remains important and has to be dealt with.